Akibat Hukum Jual Beli Hak Atas Tanah Yang Belum Bersertipikat di Kantor Pertanahan Kabupaten Buleleng - Birehina, Thomas Alexander (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 4 No 3 (2019)DO - 10.24843/AC.2019.v04.i03.p16, 2019)
Transfer of land ownership through buying and selling is done by surrendering his land as an object in the form of a certificate. This certificate is used as evidence that states the owner of the rights to his land that will be traded to the buyer. In practice, there is still land for sale in the field that does not yet have a certificate. The purpose of this research is to find out how the procedure of buying and selling land rights that have not been certified as well as the legal consequences of buying and selling land rights that are not yet certified. Empirical juridical research is a type of research in this paper. From the results of the study, the procedure that must be carried out first is by making a purchase agreement before a Notary to secure the interests of both parties, then the land is registered through a conversion at the Land Office for certificate issuance, so that the sale and purchase can be processed before the PPAT to be able to registered at the Land Office so that it is processed behind the name on behalf of the buyer. The legal consequences if the sale and purchase of land that has not been certified is not legal according to the law, unless first done through conversion at the Land Office and preceded by the making of the purchase agreement before the Notary. So that the seller's rights shift to the buyer. Pengalihan kepemilikan tanah melalui jual beli dilakukan dengan menyerahkan tanahnya sebagai obyek dalam bentuk sertipikat. Sertipikat ini dijadikan alat bukti yang menyatakan pemilik dari hak atas tanahnya yang akan diperjualbelikan kepada pihak pembeli. Pada prakteknya dilapangan masih ada tanah yang diperjualbelikan tersebut belum memiliki sertipikat. Tujuan dalam penelitian ini untuk mengetahui bagaimana prosedur jual beli hak atas tanah yang belum bersertipikat serta akibat hukum jual beli hak atas tanah yang belum bersertipikat. Penelitian yuridis empiris menjadi jenis penelitian dalam penulisan ini. Dari hasil penelitian, prosedur yang harus dilakukan terlebih dahulu adalah dengan pembuatan perikatan jual beli dihadapan Notaris untuk mengamankan kepentingan kedua belah pihak, kemudian tanahnya di daftarkan melalui konversi di Kantor Pertanahan untuk diterbitkan sertipikat, dengan begitu barulah dapat diproses akta jual beli dihadapan PPAT untuk dapat didaftarkan di Kantor Pertanahan agar diproses balik nama atas nama pembeli. Akibat hukum bilamana jual beli tanah yang belum bersertipikat tersebut dilakukan belum sah menurut hukum, kecuali terlebih dahulu dilakukan melalui konversi di Kantor Pertanahan dan didahului pembuatan perikatan jual beli dihadapan Notaris. Sehingga haknya penjual beralih kepada pembeli.